Long-term interleukin-33 treatment delays disease onset and alleviates astrocytic activation in a transgenic mouse model of amyotrophic lateral sclerosis. (June 2019) - Korhonen, Paula; Pollari, Eveliina; Kanninen, Katja M.; Savchenko, Ekaterina; Lehtonen, Šárka; Wojciechowski, Sara; Pomeshchik, Yuriy; Van Den Bosch, Ludo; Goldsteins, Gundars; Koistinaho, Jari; Malm, Tarja
Highlights: Th2-type cytokine IL-33 delayed the disease onset of female SOD1-G93 A transgenic ALS mice. IL-33 decreased the proportion of T cells in the spleens and lymph nodes of female mice. IL-33 decreased astrocytic activation in the spinal cord of female mice. Male mice were unresponsive to the treatment. Abstract: Inflammation is a prominent feature of the neuropathology of amyotrophic lateral sclerosis (ALS). Emerging evidence suggests that inflammatory cascades contributing to the disease progression are not restricted to the central nervous system (CNS) but also occur peripherally. Indeed, alterations in T cell responses and their secreted cytokines have been detected in ALS patients and in animal models of ALS. One key cytokine responsible for the shift in T cell responses is interleukin-33 (IL-33), which stimulates innate type 2 immune cells to produce a large amount of Th2 cytokines that are possibly beneficial in the recovery processes of CNS injuries. Since the levels of IL-33 have been shown to be decreased in patients affected with ALS, we sought to determine whether a long-term recombinant IL-33 treatment of a transgenic mouse model of ALS expressing G93A-superoxide dismutase 1 (SOD1-G93A) alters the disease progression and ameliorates the ALS-like disease pathology. SOD1-G93A mice were treated with intraperitoneal injections of IL-33 and effects on disease onset and inflammatory status were determined. Spinal cord (SC) neurons, astrocytes and T-cells were exposed to IL-33 to evaluate the cell specific responses to IL-33. Treatment of SOD1-G93A mice with IL-33 delayed the disease onset in female mice, decreased the proportion of CD4+ and CD8 + T cell populations in the spleen and lymph nodes, and alleviated astrocytic activation in the ventral horn of the lumbar SC. Male SOD1-G93A mice were unresponsive to the treatment. In vitro studies showed that IL-33 is most likely not acting directly on neurons and astrocytes, but rather conveying its effects through peripheral T-cells. Our results suggest that strategies directed to the peripheral immune system may have therapeutic potential in ALS. The effect of gender dimorphisms to the treatment efficacy needs to be taken into consideration when designing new therapeutic strategies for CNS diseases.